The Beastie Boys: Jews in whiteface - Stratton, Jon (Cambridge University Press, 2008)
The Beastie Boys are usually described as the white hip hop group who helped break rap to a broad-based white audience. Rarely is it acknowledged that the Beasties all came from Jewish backgrounds. This article examines the implications of the Beastie Boys’ Jewishness. The Beasties can be placed in a long history of Jewish entertainers reworking black music for white American audiences. By the 1980s, Jews in the United States had been assimilated into whiteness, yet it is clear that the memory of discrimination lived on. The members of the Beasties played with whiteness – performed in whiteface – while being very aware of their own Jewishness and the implications of this. With the advice and mentoring of African American Russell Simmons and the Jewish Rick Rubin, the group gained respect in the black community as legitimate rappers and then set out to perform as uncivil rock performers for white audiences. This article argues that the Beasties’ Jewishness was central to their success as the group that brought rap to a mainstream white American audience.